THE EFFECT OF HERRINGBONE TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION OF RECOUNT TEXT OF THE ELEVENTH GRADE - Yusinta Marisca; Meida Rabia Sihite; Linda Astuti Rangkuti (English Education Study Program FKIP Universitas Alwashliyah Medan, 2022)
The objective of this research is to find out if Herringbone Technique significantly affects students’ reading comprehension of recount text. The design applied in this research was experimental research. The population of this research was the eleventh grade of SMA Al-Hidayah Medan. There were two parallel classes: XI-A and XI-B. Each class consisted of 30 students; thus, the total number of population was 60 students. The whole population was taken as the sample. Cluster random sampling technique was applied to select the group as the research sample. Class XI-A was selected as experimental group and class XI-B was selected as control group. The instrument used to collect the data was multiple-choice test consisted of 20 items. The data were analyzed by using t-test. It was obtained that tobserved value was higher than that of ttable (3.46 > 2.00) with the degree of freedom df = 58 at the level of significance α = 0.05. It meant that Ha was accepted and Ho was successfully rejected. Thus, it can be concluded that Herringbone Technique significantly affected students’ reading comprehension of recount text.